Development of student worksheets based on guided inquiries to train students science process skills on reaction rate materials - Haridha Nurfidayanti Nurfidayanti; Bertha Yonata (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to determine the validity, practicality, and effectiveness of the worksheets developed for the chemical learning of students' reaction rates. This research is focused on the guided inquiry learning model to improve students' science process skills. The research sample was 36 students of class 11 MIPA 4 SMAN 1 Puri, Mojokerto Regency. The research model used the One Group Pretest and Posttest Design. The data analysis technique used normality test, paired sample t-test, and n-gain test. The validation results show that 93.3% is valid. An average of 98% of students showed a positive response to the developed Student Worksheets. In addition, students carry out relevant activities with 90.2% when learning takes place. The pretest-posttest of cognitive domains and science process skills showed what usually distributed the data. The paired sample t-test test showed a difference in the pretest-posttest results, and the n-gain test showed an increase in the pretest-posttest. The Student Worksheets Developed are valid, practical, and effective for use in learning chemistry for the Reaction Rate material and can train students' science process skills.